Neural correlates of word learning in children. (June 2019) - Takashima, Atsuko; Bakker-Marshall, Iske; van Hell, Janet G.; McQueen, James M.; Janzen, Gabriele
Highlights: We measured brain activity patterns for recognizing newly trained words in children. Retrieval related activation in the hippocampus decreased a week after training. Lexical integration effect was not observed even after a delay of 1 week. Younger group used right hemisphere more whereas teens used left hemisphere more. Abstract: Memory representations of words are thought to undergo changes with consolidation: Episodic memories of novel words are transformed into lexical representations that interact with other words in the mental dictionary. Behavioral studies have shown that this lexical integration process is enhanced when there is more time for consolidation. Neuroimaging studies have further revealed that novel word representations are initially represented in a hippocampally-centered system, whereas left posterior middle temporal cortex activation increases with lexicalization. In this study, we measured behavioral and brain responses to newly-learned words in children. Two groups of Dutch children, aged between 8–10 and 14–16 years, were trained on 30 novel Japanese words depicting novel concepts. Children were tested on word-forms, word-meanings, and the novel words' influence on existing word processing immediately after training, and again after a week. In line with the adult findings, hippocampal involvement decreased with time. Lexical integration, however, was not observed immediately or after a week, neither behaviorally nor neurally. It appears that time alone is not always sufficient for lexical integration to occur. We suggest that other factors (e.g., the novelty of the concepts and familiarity with the language the words are derived from) might also influence the integration process.